PENERAPAN TEKNIK EFFLEURAGE DAN PETRISSAGE TERHADAP PASIEN PENDERITA KELUHAN PADA OTOT LENGAN DI DUSUN REMAWAN - Ya' Kurnia Irawan (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Pamane Talino, 2022)
The aims of this study are (1) to find out whether the application of effleurage and petrissage techniques can alleviate the problems experienced by sufferers of arm muscle complaints in Remawan Hamlet. (2) To find out whether there is a difference between the application of manipulation of the effleurage and petrissage techniques on the problems experienced by sufferers of arm muscle complaints in Remawan Hamlet. This research is a descriptive quantitative research in the form of a survey. The subjects of this study amounted to 20 people with male criteria and the community in Remawan Hamlet. The data analysis technique used in this research is statistical calculation using percentage descriptive analysis. The results obtained that with the application of these two techniques, from 20 respondents there were 15 respondents with an average criterion of feeling